Crystallinity And Morphology Of Silicon Carbide Thin Films Deposited Using Very High Frequency Plasma Enchanced Chemical Vapor Deposition - Muizzudin, Muhamad Azali; Ismail, Abd Khamim; Omar, Muhammad Firdaus (International Journal of Engineering and Technology, 2018)
Conventional plasma enchanced chemical vapor deposition (PECVD) has been widely used since decades to deposit silicon carbide (SiC) thin film. However, lower RF frequency tends to produce hydrogenated amorphous silicon carbide (a-SiC:H) and poly-crystalline (p-SiC) type of films. This work aims to investigate the crystallinity, morphology and deposition temperature of SiC thin films at higher RF frequency. SiC thin films have been prepared on silicon substrates by using very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD). The utilisation of plasma at higher frequency is predicted to give a great impact to allow the chemical reaction at lower temperature with better crystallinity and morphology compared to conventional PECVD method. In this work, the substrate temperature and deposition time were kept constant at 400oC and 15 minutes respectively, while the RF frequency was veried between 100 MHz to 200 MHz. The crystallinity of SiC thin film samples was observed using Raman Spectroscopy while the morphology was examined under the atomic force microscopy (AFM) and scanning electron microscopes (SEM). The results shown that the crystallinity and morphology of the samples were slightly improved as frequency increases. It was observed that the surface roughness of SiC thin films is improves from 5.43 nm at 100 MHz to 13.91 nm at 200 MHz.